Comparative effect of feeding commercial milk replacer and whole milk on growth performance and feed conversion efficiency for Indian dairy calves - BHARTI, P K; KAMBOJ, M L; TYAGI, AMRISH (The Indian Journal of Animal Sciences, 2012)
Newly born crossbred dairy calves (24) of either sex were selected and equally distributed into 3 treatment groups, viz. control, treatment-1 and treatment-2, for evaluating the effect of feeding different liquid diets on their growth performances. Control group received whole milk and skim milk as per institute feeding schedule, whereas the T1 and T2 groups were fed on whole milk and milk replacer, respectively, at the constant rate 1/10th of their body weight. The birth weights of calves in control, T1 and T2 groups were 29.83±3.12, 29.66±2.47 and 30.83±3.07 kg and the final body weights were 64.00±3.39, 73.43±3.40 and 58.16±3.68 kg, respectively. The overall average daily gain (ADG) in control, T1 and T2 were 406.74±17.50, 521.03±17.00 and 325.39±13.23 g, respectively, where T1 showed significantly higher ADG than control and T2. The average daily dry matter intake in control, T1 and T2 was 0.86±0.04, 0.91±0.05 and 0.83±0.05 kg, respectively, which were nonsignificant from each other. The feed conversion efficiency in control, T1 and T2 were 2.08±1.14, 1.68±0.06 and 2.491.14, respectively, in which T1 was significantly higher than T2. The growth rate in milk replacer group was comparatively lower than whole milk and control group. The milk replacer used in the present study was more economical than feeding whole milk and skim milk. Therefore, raising crossbred calves on milk replacer could be better option for commercial dairy farms to save the saleable whole milk for human consumption.